2011
DOI: 10.4103/0974-777x.83543
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral parotid tuberculosis

Abstract: Tuberculosis of parotid is a rare clinical entity, and cases of bilateral tubercular parotitis are even rarer. We present a case of bilateral primary parotid tuberculosis in a 49-year-old female. The patient received anti-tuberculosis treatment for six months, resulting in complete resolution of the disease. We also review the theories related to the pathogenesis of tubercular parotitis, and propose a novel hypothesis about greater involvement of parotid gland as compared to other salivary glands in primary tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 25 publications
0
12
0
2
Order By: Relevance
“…[12] Isolated involvement of parotid gland by mycobacterium is rare. [10111213] Salivary gland infection is believed to be direct extension of the bacilli from the oral cavity via the gland ductal system (due to preceding tooth or tonsil infection). Hematogenous or lymphatic spread of infection is also known.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12] Isolated involvement of parotid gland by mycobacterium is rare. [10111213] Salivary gland infection is believed to be direct extension of the bacilli from the oral cavity via the gland ductal system (due to preceding tooth or tonsil infection). Hematogenous or lymphatic spread of infection is also known.…”
Section: Discussionmentioning
confidence: 99%
“…They are helpful in differentiating benign from malignant neoplasms. [10111213] In addition, they are very useful in showing whether a palpable lesion arises within the parotid gland or is periparotid in location. Radiologically tubercular parotitis can be differentiated as parenchymal and periparotid type.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been found that loss of b-catenin adhesion molecule is one of the factors responsible for development of pleomorphic adenoma and cytoplasmic accumulation of this molecule causes malignant transformation in pleomorphic adenoma. [10] Thus, the awareness of its varied clinical and histopathological presentation, recurrence, and malignant potential is instrumental on the part of the examining clinician or treating surgeon to avoid incorrect diagnosis or treatment.…”
Section: Discussionmentioning
confidence: 99%
“…2 months of HRZE * 4 months of HR Though, Tuberculosis is endemic in the Indian subcontinent, 12 tuberculosis of the parotid gland is rare and bilateral involvement is very rare. 6 The pathogenesis may be due to direct spread of mycobacteria from a nearby infected source, like tonsils or teeth and the spread may occur through direct inoculation by sputum, retrograde spread of bacilli through duct or by afferent lymphatics. Another cause may be by haematogenous or lymphatic spread from the lungs.…”
Section: Intensive Phase Treatment Continuation Phasementioning
confidence: 99%
“…13 Among the major salivary glands, parotid is the most commonly involved one by primary/pulmonary tuberculosis, whereas the submandibular glands are the most commonly involved in systemic tuberculosis. 6,1,14,15 Clinically it presents as a slow growing isolated parotid lump, painless, mobile, non-tender, diffuse or well circumscribed. It only presents as painful lump & tender, when there is abscess formation or fistula.…”
Section: Intensive Phase Treatment Continuation Phasementioning
confidence: 99%